LED Light-Activated Hypocrellin B Induces Mitochondrial Damage of Ovarian Cancer Cells - Yuan Jiang; Albert Wingnang Leung; Junyan Xiang; Chuanshan Xu (International Journal of Photoenergy)
Objective. Hypocrellin is a natural photosensitizer from a traditional Chinese herb. In the present study, our aim is to investigate the effect of LED light-activated hypocrellin B on mitochondria of ovarian cancer cells. Material and Methods. Ovarian cancer HO-8910 cells were incubated with hypocrellin B at the concentration of 2.5 μM for 5 h and then irradiated by blue light from a novel LED source. Cell survival rate of HO-8910 cells was measured using MTT assay 24 h after photodynamic treatment of hypocrellin B. Mitochondrial morphology was observed using transmission electron microscopy (TEM). Mitochondrial membrane potential was measured using flow cytometry with JC-1 staining. Results. MTT assay showed that cell survival rate of HO-8910 cells in the photodynamic treatment group has significantly decreased down to 27.22±1.26% (P<0.01). Light irradiation alone or hypocrellin B alone showed no significant impact. In our TEM mitochondria of the cells after photodynamic treatment of hypocrellin B showed severe damage with swollen mitochondria that had nearly nonexistant cristae. Mitochondrial membrane potential remarkably decreased after photodynamic action of hypocrellin B. Conclusion. The findings demonstrated that photodynamic action of hypocrellin B significantly decreased cell proliferation of ovarian cancer HO-8910 cells, caused severe damage to mitochondrial structure, and induced mitochondrial membrane collapse.